Para gostar de matemática: uma proposta de atividades destinada ao professor no Nível fundamental - Lima, Claudio Roberto Agra (2015)
The inspiration for this work was born from the realization that mathematics teaching in public schools has shown poor results in national assessments, that worsen with the advancement of the level of education, particularly in Sao Miguel dos Campos. An extension project was developed with interventions in two groups of 6th grade of a Municipal School, with the aim of presenting in class activities room and mathematical games that rescued the fascination provided by the mathematical knowledge throughout the history of mankind, arousing greater interest in students. The selected activities were combined in guide for elementary school teachers, as a legacy of this project.